2009
DOI: 10.1097/brs.0b013e31819c09c4
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Anular Changes Induced by Puncture Are Associated With Insufficiency of Disc Biomechanical Function

Abstract: Our findings suggest that injury sizes large enough to disrupt biomechanical function are needed to drive degenerative changes in rat caudal disc AF. Based on the data, we believe that small anular defects become sealed, allowing the disc to function normally and the AF to heal. Larger defects appear to require longer wound closure times, and may prolong the duration of impaired disc function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 65 publications
5
90
0
Order By: Relevance
“…Furthermore, recent studies have shown that the degenerative process within a disc can be initiated with a mere needle puncture, i.e. performed during lumbar discography [27,[38][39][40][41][42][43][44][45][46]. Therefore, discography was not employed as a diagnostic tool in the present study.…”
Section: Preoperative Diagnosis and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have shown that the degenerative process within a disc can be initiated with a mere needle puncture, i.e. performed during lumbar discography [27,[38][39][40][41][42][43][44][45][46]. Therefore, discography was not employed as a diagnostic tool in the present study.…”
Section: Preoperative Diagnosis and Patient Selectionmentioning
confidence: 99%
“…Degenerative changes resulting from lumbar degenerative disc disease (DDD) have been associated with a negative impact on the clinical manifestation of LBP. Hereditary as well as mechanical factors have been discussed in the pathogenesis of DDD, and experimental studies demonstrated that the degenerative cascade can be initiated with a mere needle puncture into the disc [27,38,40,[43][44][45][46][61][62][63]. Once initiated, the degenerative process is progressive, irreversible and closely associated with a mechanical dysfunction of the affected segment.…”
Section: Lumbar Degenerative Disc Diseasementioning
confidence: 99%
“…For the MRI assessment, the caudal segments 5/6 and 7/8 from the same rat tail were interchangeably used for the gel alone treatment and HGF treatment. After identifying the level of the caudal segments by fluoroscopy, a puncture was made parallel to the endplates through the annulus fibrosus (AF) into the NP by a syringe needle (21-gauge) (12). The needle was then rotated by 180˚ and held for 5 sec.…”
Section: Introductionmentioning
confidence: 99%
“…However, in another study using the same animal model, only 18 gauge needle punctures led to significant changes in disc biomechanics; these changes were not seen in 22-and 26-gauge punctured discs [37].…”
Section: Further Development Of the Micro-osmometer Techniquementioning
confidence: 99%